Tinjauan Fikih Muamalah terhadap Jual Beli Photocard pada Album Kpop - Selvira Eka Suci; Asep Ramdan Hidayat; Yayat Rahmat Hidayat (UNISBA Press, 2022)
Abstract. The development of technology is increasingly advanced, making it easier for people to find and get information from outside, especially online media. The rapid development of online media makes it easier for people to get new lessons about foreign cultures, which indirectly affects people as online media users. The outside culture that quite influences teenagers includes South Korea through its entertainment industry from the field of music or better known as kpop or Korean Pop. As a form of support for the preferred group, fans are usually willing to do many things, one of which is buying albums and collecting photocards. Based on this phenomenon, the problems that can be formulated are as follows: (1) the practice of buying and selling kpop album photocards